Review Article: Comparison of three types of polymers Delrin , Polyester and Nylon - Kawther A. alwahid abdulhameed; Attiya H .G; Ruwaidah S. Saeed (Journal of Madenat Alelem University College, 2024)
This article discusses three types of manufactured polymers: Delrin, nylon, and polyester. Polymers are the product of various forms of raw plastics found in nature, whereas plastics are the names given to chemically human-made polymers. Polymer substances consist of a single unit called a monomer, which binds to millions of other similar molecules to form long chains. The length of these chains, the number of branches, and how closely they relate to each other determine the physical properties of the final plastic Polymers and their privileged position in chemistry due to their chemical and physical properties. The strength of the polymer depends on the number of monomers along the chain, side groups, cross-links and branches. If the polymers consist of only one type of monomer, it is called a homopolymer, and if there is more than one monomer in the polymer series, it is called a copolymer. Increasing the length of the chain polymers leads to a high degree of colour acceptance, describing the existence of polymers with different colours. Many chemical names of polymers were used, such as plastics, and became familiar to consumers.